2013
DOI: 10.4102/sajems.v16i5.640
|View full text |Cite
|
Sign up to set email alerts
|

A research on comprehension differences between print and screen reading

Abstract: Since the 1980s, extensive research has been conducted comparing reading comprehension from printed text and computer screens. The conclusions, however, are not very consistent. As reading from computer screens requires a certain degree of individual technical skill, such variables should be objectively taken into consideration when conducting an experiment regarding the comparison between print and screen reading. This study analyses the difference in the level of understanding of the two presentational forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 66 publications
3
11
0
1
Order By: Relevance
“…Moreover, we believe that because most of these tests were administered to individuals who are not truly 'digital natives', it would be hasty to draw definite conclusions with regard to on screen reading performance. Above all, individual digital skills and literacy are important factors as Sun, Shieh and Huang (2013) remind us: "Reading from computer screens requires a certain degree of individual technical skill. However, most researchers did not objectively take the variable into account when conducting an experiment regarding the comparison between print and screen reading."…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we believe that because most of these tests were administered to individuals who are not truly 'digital natives', it would be hasty to draw definite conclusions with regard to on screen reading performance. Above all, individual digital skills and literacy are important factors as Sun, Shieh and Huang (2013) remind us: "Reading from computer screens requires a certain degree of individual technical skill. However, most researchers did not objectively take the variable into account when conducting an experiment regarding the comparison between print and screen reading."…”
Section: Resultsmentioning
confidence: 99%
“…Another study published in the same year found that once participants had acquired a certain degree of technical skill, there was little difference in comprehension outcomes between learners reading on screen or paper (Sun et al, 2013). Further they found that the ability of hypertext ability to integrate information within electronic documents had a positive effect on cognitive processing for middle-age learners, facilitating a deeper understanding of the content.…”
Section: Screen Vs Paper Researchmentioning
confidence: 98%
“…One was driven by the need to find particular information or fact for a specific purpose. The other linear form involved concentration and emotional engagement (Durant & Horava, 2015;Sun et al, 2013). More recently, hypertexts within electronic documents allow readers to leave one resource and explore a range of alternative resources, providing a less linear, reading experience (Anderson-Inamn & Horney as cited in I-Chia, 2012).…”
Section: Reading Theorymentioning
confidence: 99%
See 2 more Smart Citations